Defect induced photoluminescence and triboluminescence in layered CaLaAl3O7. Issue 13 (15th November 2019) - Li, Yezhou; Koskin, Igor P.; Ma, Zhidong; Benassi, Enrico; Wang, Zhaofeng
Abstract : Attractive photoluminescence and triboluminescence were demonstrated in layered CaLaAl3 O7, and the intrinsic defect effects were investigated. Abstract : In this work, a layered melilite structure, CaLaAl3 O7, was synthesized and observed to have obvious luminescence behaviors under the stimuli of ultraviolet light and rubbing, which were called photoluminescence and triboluminescence, respectively. Considering the wide bandgap of CaLaAl3 O7 and its specific crystal structure, the observed luminescence should be attributed to intrinsic defects. Both the photoluminescence and triboluminescence of CaLaAl3 O7 show a strong dependence on the synthesis atmosphere, suggesting that they should be related to the oxygen vacancy. It is attractive to find that the triboluminescence of CaLaAl3 O7 shows a distinct spectral characteristic compared to its photoluminescence. Further computational results suggest that the applied mechanical stimuli on the CaLaAl3 O7 cell could promote the formation of the vacancies of oxygen and calcium, responsible for the spectral differences.